2020
DOI: 10.3390/nu12072007
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Bovine Whey Derived Oligosaccharides Showing Synbiotic Epithelial Barrier Protective Properties

Abstract: Commensal gut microbiota and probiotics have numerous effects on the host’s metabolic and protective systems, which occur primarily through the intestinal epithelial cell interface. Prebiotics, like galacto-oligosaccharides (GOS) are widely used to modulate their function and abundance. However, important structure–function relations may exist, requiring a detailed structural characterization. Here, we detailed the structural characterization of bovine whey derived oligosaccharide preparations enriched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Briefly, the paired-end reads were merged, quality filtered, and split into libraries as described by Monaco et al [37]. Operational taxonomic units (OTU) assignment, representative sequence picking, chimera removing, sequence alignment, and phylogenetic tree construction were performed as previously described [17]. Taxonomic assignment for each representative sequence was done using Ribosomal Database Project naïve Bayesian rRNA Classifier at 80% confidence level on the Greengenes reference database (gg_13_8_otus/taxonomy/97_otu_taxonomy.txt, accessed on 24 February 2017) [44].…”
Section: Sequence Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, the paired-end reads were merged, quality filtered, and split into libraries as described by Monaco et al [37]. Operational taxonomic units (OTU) assignment, representative sequence picking, chimera removing, sequence alignment, and phylogenetic tree construction were performed as previously described [17]. Taxonomic assignment for each representative sequence was done using Ribosomal Database Project naïve Bayesian rRNA Classifier at 80% confidence level on the Greengenes reference database (gg_13_8_otus/taxonomy/97_otu_taxonomy.txt, accessed on 24 February 2017) [44].…”
Section: Sequence Processingmentioning
confidence: 99%
“…Several studies have reported beneficial effects of feeding HMO and bovine milk derived oligosaccharides (BMOS), including modulation of growth [ 12 ], alkaline phosphatase activity [ 13 ], gene transcription [ 14 ], and barrier function [ 15 , 16 , 17 ] of the intestinal epithelial cell in vitro. HMO also influence the development of the immune system [ 18 , 19 ] and the brain [ 20 , 21 ] and shape the development of the infant gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…GOS have various benefits to human health including the selective stimulation of the beneficial intestinal bacteria growth, maintenance of the normal flora balance in the intestine, increased calcium absorption, and decreased serum cholesterol levels and cancer risks. The health-promoting effects of GOS include immunomodulation, lipid metabolism, mineral absorption, weight management, and obesity-related issues, among others [ 64 , 65 , 66 ].…”
Section: Hydrolyzed Protein From Milk Whey As High Value-added Compoundsmentioning
confidence: 99%